(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides an overview of the system algorithm that helps in selecting qualified personnel from a system based on fuzzy logic in real time using the Fuzzy Logic Toolbox package in the Matlab environment, which is a product of Mathworks, by forming a Mamdani-type fuzzy logic model based on a set of important rules used to select the necessary frames from the system, and as a result, based on fuzzy sampling rules that can be included in the model of the algorithm of the master system and a three-dimensional graphical representation of this model is considered